Physiotherapy clinical educator's needs - N. P. Mbambo (AOSIS, 1999)
Physiotherapy clinicians have been involved in student clinical education since the early days of physiotherapy training. As the physiotherapy practice and student learning has changed over the last three decades, so have the role of the clinical educators. Little has been done though, to prepare or support the clinical educators in this new role which is more complex. The needs of the clinical educators in terms of their involvement in clinical education and their training for this role are established and recommendations are made to meet these needs.